Changes in dynamic and static brain fluctuation distinguish minimal hepatic encephalopathy and cirrhosis patients and predict the severity of liver damage - Ji, Jiang; Liu, Yi-yang; Wu, Guo-Wei; Hu, Yan-Long; Liang, Chang-Hua; Wang, Xiao-dong (Frontiers in Neuroscience, 2023)
Purpose: Minimal hepatic encephalopathy (MHE) is associated with an elevated risk of developing into a severe neuropsychiatric syndrome and is undetectable by routine clinical exams. In previous neuroimaging studies, abnormal static brain activity and connectivity have been observed in MHE patients. However, little is known concerning temporal dynamic intrinsic brain activity. More extensively, it is unclear whether altered brain dynamics of brain activity could better distinguish MHE patients from cirrhotic patients. Methods: We included 34 cirrhotic patients with MHE, 28 patients without MHE, and 33 age-, sex-, and education-matched healthy controls (HCs) who underwent resting-state magnetic resonance imaging (rs-fMRI). We then adopted a sliding-window method to estimate dynamic low-frequency fluctuation amplitude (dALFF), by which temporal variability was quantized over the whole-scan timepoints and then compared among the three groups. Additionally, dynamic and static ALFF values were utilized as classification features in a linear support vector machine (SVM) to distinguish MHE patients from those without minimal hepatic encephalopathy (noMHE). Results: Compared with HCs, MHE patients showed significantly increased dALFF in the left inferior occipital gyrus, right middle occipital gyrus, and right insula, while the increased dALFF was located in the right cerebellum posterior lobe (CPL) and right thalamus. Compared with HCs, noMHE patients demonstrated decreased dALFF in the right precuneus. In contrast, when compared with noMHE patients, MHE patients showed increased dALFF in the right precuneus, right superior frontal gyrus, and right superior occipital gyrus. Furthermore, the increased dALFF values in the left precuneus were positively associated with poor DST scores (r = 0.356, p = 0.038); however, the right inferior temporal gyrus (ITG) was negatively associated with poor NCT-A scores (r = -0.784, p = 0.000). A significantly positive correlation was found between the increased dALFF in the left inferior occipital gyrus (IOG) and high blood ammonia levels (r = 0.424, p = 0.012). Of interest, dALFF characteristics have a higher classification accuracy than sALFF characteristics in distinguishing MHE patients from cirrhotic patients. Conclusions: This study provides novel insight into understanding MHE-related mechanisms and highlights the important role of dynamic neural activity in informing the diagnosis of MHE.